2016
DOI: 10.1007/s11481-016-9675-8
|View full text |Cite
|
Sign up to set email alerts
|

Brain Microstructure and Impulsivity Differ between Current and Past Methamphetamine Users

Abstract: Methamphetamine (Meth) use disorder continues to be highly prevalent worldwide. Meth users have higher impulsivity and brain abnormalities that may be different between current and past Meth users. The current study assessed impulsivity and depressive symptoms in 94 participants (27 current Meth users, 32 past Meth users and 35 non-drug user controls). Additionally, brain microstructure was assessed using diffusion tensor imaging (DTI); fractional anisotropy (FA) and mean diffusivity (MD) were assessed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…As previously indicated, METH users also display affective symptoms, including depression (London et al, 2004), psychotic symptoms (Sekine et al, 2002(Sekine et al, , 2003, impulsivity (Andres et al, 2016), or aggressive behavior (Sekine et al, 2006). Sensitization to METH psychosis could be functionally related to neurotoxicity because psychiatric symptoms correlated inversely with DAT density in the striatum and PFC (Sekine et al, 2003).…”
Section: Molecular Mechanisms and Loci Of Meth Neurotoxicitymentioning
confidence: 88%
“…As previously indicated, METH users also display affective symptoms, including depression (London et al, 2004), psychotic symptoms (Sekine et al, 2002(Sekine et al, , 2003, impulsivity (Andres et al, 2016), or aggressive behavior (Sekine et al, 2006). Sensitization to METH psychosis could be functionally related to neurotoxicity because psychiatric symptoms correlated inversely with DAT density in the striatum and PFC (Sekine et al, 2003).…”
Section: Molecular Mechanisms and Loci Of Meth Neurotoxicitymentioning
confidence: 88%
“…Inhibitory control and impulsivity are associated (129). Indeed, people with schizophrenia or meth use disorder both display poor impulse control (24,25,36,38,42,130,131). Notably, impulse-related functions are among the most impaired in meth use disorder (76), and poor impulsivity is regarded as one key predisposing factor to developing substance use disorder (132).…”
Section: Inhibitory Controlmentioning
confidence: 99%
“…Meth dependents also display structural abnormalities in the genu of the corpus callosum (138,139), a white matter tract which carries fibers originating from the PFC. Poorer corpus callosum integrity is associated with impaired inhibition (140,141) and impulse control (38). In addition to structural abnormalities, people with meth use disorder display reduced activation of the PFC when performing the Stroop task (56), more specifically in the right inferior frontal gyrus (IFG), ACC (23) and the PFC (26).…”
Section: Inhibitory Controlmentioning
confidence: 99%
“…Increased putamen grey matter volume (Moreno-Alcázar et al, 2018) and cerebral blood flow (Filbey, Aslan, Lu, & Peng, 2018) have been shown in healthy cannabis users compared to controls. Increased putamen volume has been shown to be associated with methamphetamine use (Andres et al, 2016;Chang et al, 2005;Jan, Lin, Miles, Kydd, & Russell, 2012), with alterations in putamen myeleoarchitecture in those at behavioural risk of addiction (Nord et al, 2019), and increased putamen volumes in probands with stimulant addiction and relatives of those with addictive disorder (Ersche et al, 2012). Two previous studies have examined cannabis use in the context of psychosis: one showed putamen volume increases in cannabis-using compared to non-using PwP (Koenders et al, 2015), whereas the other found neurochemical changes in the left putamen with higher NAA/choline ratio in cannabis-using PwP compared to controls (Malchow et al, 2013).…”
Section: Discussionmentioning
confidence: 99%